Sistem Pendeteksi Banjir dengan Sensor Ultrasonic berbasis Mikrokontroller di kota Pangkalpinang - Septryanti, Ade; Magdalena, Hilyah; Santoso, Hadi; Juhri, Juhri (Jurusan Teknologi Informasi Universitas Semarang, 2022)
Provide convenience and information to BPBDs and people living in flood-prone environments that are usually unknown to homeowners without getting information about the arrival of floods in the area. So we need a system that can detect the water level of the river. For that, it is necessary to install a device that can read the water level in the form of an ultrasonic sensor and a microcontroller as well as a GSM SIM900A module. The research method used is literature study, problem analysis, system design and implementation.The results achieved in this study are able to help provide information in the form of sirens and SMS services in the form of short messages about flood alert levels that are sent to the community and the BPBD.